Ambivalent influencers: Feeling rules and the affective practice of anxiety in social media influencer work - Lehto Mari (Sage Journals, 2022)
This article investigates the intimate cultures of Finnish influencer mothers. Through in-depth qualitative interviews with four Finnish influencer mothers and online observation of their social media accounts, the article asks how influencers negotiate the feeling rules that govern maternal femininity on social media and attempt to cope with the emotional weight of precarious social media work. The article argues for using the affective practice of anxiety as a theoretical concept to explore the influencers’ routinized emotional behaviour in their attempts to decrease the discrepancy between their emotions and cultural expectations. The article suggests that although anxiety can be considered a negative side effect of stressful social media work, sharing it on social media can also be understood as a tactic that plays a central role in the lifestyle influencer industry. Drawing on Loveday’s analysis of the ‘neurotic academic’, the article suggests that the construction of an entrepreneurial influencer self is underpinned by anxiety. This argument is formulated through the figure of the ‘neurotic influencer’ that is the embodiment of the ambivalent nature of gendered influencer work.